PENERAPAN METODE TOPSIS DALAM PENILAIAN KINERJA GURU TETAP SD NEGERI KEBALEN 07 - Susliansyah, Susliansyah; Rahadjeng, Indra Riyana; Sumarno, Heny; Deleaniara. M, Chyntia Marianna (LPPM Universitas Nusa Mandiri, 2019)
To find out the problems faced in the teaching performance assessment process by utilizing the Technique For Order Preference method by Similiarity to Ideal Solution (TOPSIS), to manage the processing of Teacher data is a more optimal consideration. By using the (TOPSIS) method as a basis for processing teacher performance assessment data. This can allow the system to provide an assessment in accordance with the quality of each teacher and is expected to facilitate decision making in the assessment of Teacher's performance. The Technique For Order Preference by similiarity to Ideal Solution has been running well and can result in a weighting of assessment criteria and clear and fast information compared to manual calculations so SD Negeri Kebalen 07 can use it as a tool for making appropriate decisions.